(untitled) (Biocenosis, 2024)
The present investigation corresponds to a mixed-method approach, which was carried out at the Caño Negro National Wildlife Refuge (RNVSMCN), located in Alajuela, Costa Rica (10°52‘37“N 84°45‘47“W). The methodology involved both terrestrial and aquatic surveys within the refuge. Sampling was conducted through on-site observation, and photographs were taken as resources for flora and fauna, focal element selection and graphic material design. The participants in the study were RNVSMCN officials. Social surveying consisted of semi-structured interviews, expert panels, and focal groups; the selection of the target audience was based on social media visitation statistics. A total of 192 visual products were obtained in the informal education category (to be distributed on Facebook and Instagram platforms) comprising a visual compendium called Social Media Content Calendars. The main objective of this proposal was Scientific Outreach on social networks, through visual posters with original photographs aimed at promoting environmental education, focusing on young adults (18-35 years old) not specialized in biological topics, in order to foster ecosystem conservation and biodiversity preservation within the refuge.